Notion of a legal entity in the Сivil Code of the Republic of Belarus: current state and development prospects - Salei, Alena A. (Journal of the Belarusian State University. Law, 2019)
The notion of a legal entity is analyzed in the context of Belarusian civil legislation reforming. The amendments to the Civil Code announced for public discussion are being assessed. Certain proposals on improvement of national material and conflict legislation on legal entities aimed at inter alia harmonization of legislation within the Eurasian Economic Union are made.
Keywords: legal entity; commercial organization; non-profit organization; corporation; company name; state registration; law of legal entity